The Repressive Nature of Local Regulations on Tolerance in Indonesia - Hadi, Sahid; Heron, Heronimus (Jurnal Hukum IUS QUIA IUSTUM, 2026)
This article investigates the nature of local regulations on tolerance in Indonesia. Focusing on considerations that shape the primary rationales of such local regulations, this article explains the repressive approach that local governments in Indonesia have persistently used in responding to religious intolerant incidents. Applying a conceptual framework concerning the social conflict prevention-management and human rights approach and drawing on a content analysis of 12 local regulations, the consideration of preventing and managing social conflicts has dominated the primary rationales of local regulations on tolerance in Indonesia. In contrast, human rights considerations, particularly those focused on protecting freedom of religion and belief to promote greater religious diversity, remain marginal across the regulatory corpus. Instead of serving as a tool for promoting individual freedoms and diversity, existing local regulations on tolerance function as instruments that suppress diversity, working on the assumption that religious differences inherently pose a threat of social friction. Drawing on a critical understanding that pro-tolerance regulatios may be used as repressive tools to suppress religious diversity, we argue for human rights-based approach, as well as individual freedoms, to promote religious diversity and as a reference point for developing tolerance regulations in Indonesia.